Evaluation of the development of sorghum (sorghum bicolor l. Moench) due to different fertilizers and plant densities at 60 and 90 days of emergence - Lisboa, Samila Barbosa; Gonçalves, Saulo Venâncio da Silva; Beserra, Theóphilo Michel Alvares Cabral; Bezerra, Rickson Tavares; Fontenele, Rildson Melo (Seven Editora, 2023)
The culture of sorghum (Sorghum bicolor L. Moench) disseminated throughout the country, has a relevant importance for northeastern agriculture. An alternative to providing an increase in the productive parameters of this forage is the use of organic compounds. Therefore, the objective of this work was to evaluate sorghum production as a function of different plant spacing and fertilization with organic sources. The experimental design was in randomized blocks (DBC) in a 4x2 factorial scheme, four treatments, of these, three are sources of fertilizers (cattle manure, sheep manure, and commercial NPK1010) plus the control, and two sowing densities 10 and 15 plants per linear meter, with four replications. The preparation of the area for implantation was mechanized, and the planting of the black tip sorghum was carried out manually with a spacing of 0.70 m between rows and 1.5 m of length in each plot. After 60 days of sowing, an evaluation of forage development was performed by evaluating the variables: plant height (AP), stem diameter (DC), and number of leaves (NF). And 90 days after emergence, a second growth assessment was performed. The data were submitted for analysis using Tukey’s test (P≤0.05) with the aid of SISVAR software. Given the data, we can conclude that, of the variables studied in this study, at 60 days the treatment using sheep manure was denoted to have negatively influenced the number of leaves, however, at 90 days it obtained higher averages, than the other treatments, in plant height and number of leaves in both densities. DOI:https://doi.org/10.56238/alookdevelopv1-057